Analysis of Firms’ Characteristics Affecting the Sustainability Reporting Disclosure in Malaysia - Nazaria, Md. Aris; Suzila, Mohamed Yusof; Nur ‘Izzah Imani, Idris; Razman, Anuar; Nurul Syuhada, Zaidi (International Journal of Academic Research in Busines and Social Sciences., 2021)
In today’s dynamic and challenging business environment, the numbers in company’s financial statements alone do not represent full information on company's overall performance demanded by various parties. Behind the numbers, companies are obliged to report on the economic, environment, social and governance factors that impact their business daily activities. Thus, companies embed sustainability reporting in response in taking the economic, social and environmental performance into account. This paper concerns to analyse the effect of firm characteristics’ proxied by firms size (FSZ), firms type (FTY) profitability (PRO), and achievements (ACH) towards sustainability reporting disclose (SRD). The control variable in this study is internal goals (ING) of the company. There are four types of theories that are related with this study, which are institutional theory, legitimacy theory, stakeholder theory and agency theory. Of the data collected from 60 companies’ annual report in Bursa Malaysia for three years from 2014 to 2016, the results revealed that company’s size, profitability and achievements have significant relationship with sustainability reporting disclosure. This study is important study to companies in Malaysia to sustain their business and competitiveness over the long term in order to attract the investors. This study contributes insight for managers to improve on the disclosure of material narrative statement in their annual reports. Not only this study benefits companies and managers but also to investors as they are interested to understand how organisations correspond to the risks and opportunities of non-financial matters such as economic, environment, social and governance.